Magic Farm A big surprise! - Birch, Ashley; Chaffey, Samantha (Egmont London, 2011)
"Oliver and their friend Aidan are back on Magic Farm, and the Hayseeds are in a flap again. Those pesky Little Rotters have upset the sheep, and now the lambs are in danger! With the help of a sheep-goose and a magical farm machine called The Duzzit, the children are able to save the day."--Back cover